14-3-3 binding sites in the Snail protein are essential for Snail-mediated transcriptional repression and epithelial-mesenchymal differentiation - Hou, Zhaoyuan (2010)
The Snail transcription factor is a repressor and a master regulator of epithelial-mesenchymal transition events (EMT) in normal embryonic development and during tumor metastases. Snail directly regulates genes affecting cell adhesion, motility and polarity. Invasive tumor cells express high levels of Snail and it is a marker for aggressive disease and poor prognosis. Transcriptional repression and EMT induction by Snail requires binding to its obligate corepressor, the LIM protein Ajuba. It is unclear how this complex is assembled and maintained on Snail target genes. Here we define functional 14-3-3 binding motifs in Snail and Ajuba which selectively bind 14-3-3 protein isoforms. In Snail, a NH(2)-terminal motif in the repression domain cooperates with a COOH-terminal, high affinity motif for binding to 14-3-3 proteins. Coordinate mutation of both motifs abolishes 14-3-3 binding and inhibits Snail-mediated gene repression and EMT differentiation. Snail, 14-3-3 proteins, and Ajuba form a ternary complex which is readily detected via ChIP at the endogenous E-cadherin promoter. Collectively, these data show that 14-3-3 proteins are new components of the Snail transcriptional repression machinery and mediate its important biological functions.